The Effect of Beverage Type and Exposure Duration on Bond Strength Between Zirconia- Based CAD/CAM Ceramic and Resin Cement - Yersel, Goktug (2026)
This in vitro study aimed to evaluate the effects of beverages with different pH levels and various storage durations on the shear bond strength (SBS) of CAD-CAM zirconia bonded with dual-cure resin cement. A total of ninety specimens were prepared using CAD-CAM zirconia (Katana Zirconia, Kuraray, Japan) and a dual-cure resin cement (Panavia V5, Kuraray, Japan). The specimens were randomly divided into three groups according to the storage solution: distilled water, mineral water, and cola. Each group was further subdivided into three time intervals: 24 hours, 30 days, and 90 days (n=10 per subgroup). All specimens were stored at room temperature and exposed to the respective solution for 20 minutes daily. Shear bond strength testing was performed using a universal testing machine, and the results were analyzed by one-way ANOVA at a significance level of α=0.05. The statistical analysis revealed no significant effect of the type of beverage (p=0.114), storage time (p=0.214), or the interaction between them (p=0.433) on SBS values. Although the lowest bond strength was observed in specimens stored in cola for 90 days (11.95±3.32 MPa), this difference was not statistically significant. The highest value was recorded in the distilled water group at 24 hours (18.65±5.93 MPa). Within the limitations of this study, the type of beverage and exposure duration did not significantly affect the shear bond strength of the zirconia-resin cement interface. However, acidic beverages such as cola may demonstrate a trend toward decreased bond strength following prolonged exposure.